Information and Communication Technology (ICT) Integration in Teaching English for Young Learners - Wati, Siska Oktawidya; Zaim, M.; Thahar, Harris Effendi (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Information and communication technology is not a new issue in education world, but it is interesting to follow its development. Teachers can use this kind of technology to increase work ethos. Besides, this technology makes it possible to do many kinds of activity fast, precisely, and accurately. The development of information technology shows that there appears varieties of activity based on technology. Teaching English as second language becomes more challenging to teach, particularly for young learners. The research method used Systematic Literature Review, namely a literature search both international and national using the Google Scholar website. Data collection was carried out by documenting and reviewing all articles related to ICT media in English for young learners. So it can be concluded that the use of ICT media in early childhood English learning can be done and has a positive impact that benefits both teachers and children.